Uses of entropy in medical research - Neal, Alexander (CES Medicina, 2008)
Entropy is a basic concept of physics, with analogues in communication theory and other fields. We review applications of entropy in medical research, under three headings of increasing scientific profundity. First, we consider the use of entropy as a summary statistic to measure the diversity of ecological and other systems. We emphasize the exponential of the Shannon entropy as a dispersion index, illustrated in sample size determination for pupal surveys of the dengue vector mosquito Aedes aegypti. Secondly, we review maximum entropy as a method of statistical modelling, illustrated by spatial analysis of the malaria vector mosquito Anopheles nuñeztovari. Finally, we review the postulate of Extreme Physical Information (EPI), which elegantly yields many key laws ofphysics, including general relativity. EPI has been applied to some biological problems, such as predicting rates of cancer growth, and we suggest that it may have fruitful applications in immunology.